2013
DOI: 10.1021/ie400813v
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Mechanical Characterization of Nanostructured Thermosets from Epoxy and Styrene-block-Butadiene-block-Styrene Triblock Copolymer

Abstract: Styrene-block-butadiene-block-styrene (SBS) triblock copolymers epoxidized at several epoxidation degrees by hydrogen peroxide in water/dichloroethane biphasic system were blended with epoxy based on diglycidyl ether of bisphenol A (DGEBA) and DDM (4,4′-diaminodiphenyl methane) as curing agent. The incorporation of epoxidized block copolymers in epoxy resulted in the formation of nanostructured blends. The morphologies of the blended polymers were studied using field emission scanning electron microscopy (FESE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 54 publications
3
47
0
Order By: Relevance
“…In this study, neat epoxy showed a K IC value of about 1 MPa m 1/2 . Because the critical stress intensity value of the 10 wt % epoxidized polystyrene-block-poly(n-butyl acrylate)-block-polystyrene in DGEBA/DDM blends was slightly higher than that of the neat epoxy, as reported in literature, 29 the 69% increase in K IC of the 10 wt % SMA-SBAS in the DGEBA/DDM blends was attributed to the strong interfacial adhesion between reactive BCP and the epoxy matrix. Cured blends containing 5 and 10 wt % of SMA-SBAS with nanospheres and vesicles imparted 31 and 69% increases in K IC , respectively.…”
Section: K Icsupporting
confidence: 67%
See 1 more Smart Citation
“…In this study, neat epoxy showed a K IC value of about 1 MPa m 1/2 . Because the critical stress intensity value of the 10 wt % epoxidized polystyrene-block-poly(n-butyl acrylate)-block-polystyrene in DGEBA/DDM blends was slightly higher than that of the neat epoxy, as reported in literature, 29 the 69% increase in K IC of the 10 wt % SMA-SBAS in the DGEBA/DDM blends was attributed to the strong interfacial adhesion between reactive BCP and the epoxy matrix. Cured blends containing 5 and 10 wt % of SMA-SBAS with nanospheres and vesicles imparted 31 and 69% increases in K IC , respectively.…”
Section: K Icsupporting
confidence: 67%
“…20 The main concept of BCPs in modifying epoxy blends is their miscibility in epoxy blends. [28][29][30] In previous studies, the reactive groups introduced into the BCPs were not able to react with DGEBA or were randomly distributed. 16,19,[21][22][23][24][25][26] In the cases where the BCP does not have any segments miscible with the epoxy resin, it is essential to chemically modify one of the blocks to make it miscible with the epoxy resin.…”
Section: Introductionmentioning
confidence: 99%
“…5 a. The large specific surface areas can be provided by nano-sized PPO particles, which will help stress transfer between PPO particles and BCE/EP matrix [32]. Nano-sized PPO particles have very high surface areas and thus relatively more energy will be consumed due to the nano-sized PPO particles to prevent the production of microcracks and propagation of the flaws when the samples suffer impact testing, and hence contributing to the improvements in the impact resistance.…”
Section: Flexural and Impact Toughness Properties Of Compositesmentioning
confidence: 99%
“…In general, the compatibility between the polymer phases decides the properties of a heterogeneous polymer blend [6,7]. The interface between the polymer phases in a polymer system is characterized by the interfacial tension which, when approaching zero, causes the blend to become miscible.…”
Section: Compatibility In Polymer Blendsmentioning
confidence: 99%